1978
DOI: 10.1007/bf01072469
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma motilin concentration and gastrointestinal contractile activity in conscious dogs

Abstract: Simultaneous measurement of plasma motilin concentration and gastrointestinal contractile activity was make in 12 healthy dogs. Plasma motilin concentration was measured by radioimmunoassay and gastrointestinal contractile activity was monitored by means of chronically implanted force transducers. During the interdigestive state, it was found that the plasma motilin concentration increased in complete accordance with the cyclical interdigestive contractions of the stomach. Furthermore, plasma motilin concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(106 citation statements)
references
References 14 publications
6
99
1
Order By: Relevance
“…In the Fall of 1976, while we were investigating a possible relationship between plasma gastrin levels and phasic activities of interdigestive myoelectric complex, the motilin level revealed a cyclic increase and the peak concentration was observed in phase III of the proximal duodenal myoelectric activity in dog (Fig 3). A similar observation was made by Itoh et al (Itoh et al, 1978). The cyclic increase occurred regardless of the presence or absence of acid in the stomach (Fig 4) .…”
supporting
confidence: 70%
See 1 more Smart Citation
“…In the Fall of 1976, while we were investigating a possible relationship between plasma gastrin levels and phasic activities of interdigestive myoelectric complex, the motilin level revealed a cyclic increase and the peak concentration was observed in phase III of the proximal duodenal myoelectric activity in dog (Fig 3). A similar observation was made by Itoh et al (Itoh et al, 1978). The cyclic increase occurred regardless of the presence or absence of acid in the stomach (Fig 4) .…”
supporting
confidence: 70%
“…Using the immunoassay method Itoh et al, 1978 ;Tai and Chey, 1978), the plasma level of motilin has been measured and the relationship between the plasma levels of motilin and the proximal duodenal motility has been investigated. In the Fall of 1976, while we were investigating a possible relationship between plasma gastrin levels and phasic activities of interdigestive myoelectric complex, the motilin level revealed a cyclic increase and the peak concentration was observed in phase III of the proximal duodenal myoelectric activity in dog (Fig 3).…”
mentioning
confidence: 99%
“…It has been demonstrated that plasma motilin is released at ϳ100-min intervals during the interdigestive state and induces phase III contractions of MMC in humans (45) and dogs (20). However, in rodents, although specific phase III-like contractions were observed every 15 min in the fasted state (7,48), many reports claimed that administration of motilin or a motilin agonist failed to stimulate contraction of rat intestinal muscle strips and gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that plasma motilin is released at ϳ100-min intervals at the interdigestive state (20,21). Physiological study of motilin in vivo has been mainly performed by using dogs and humans, and endogenous motilin and exogenous motilin have been shown to induce phase III contractions through the cholinergic pathway because atropine pretreatment completely abolished the motilin-induced contractions (11).…”
mentioning
confidence: 99%
“…It has been shown that plasma concentration of motilin changed in a cyclic fashion and that it has rhythmus occurring every 90-100 min. In fact, administration of motilin has been shown to induce phase III-like contraction via the cholinergic pathway, and endogenous motilin is thought to be physiologically important for phase III contraction (Vantrappen, et al 1979) (Itoh, et al 1978). Since the ghrelin receptor is expressed in the gastrointestinal tract, the effect of ghrelin on gastric motility has also been examined.…”
Section: Roles Of Motilin and Ghrelin In Gastric Motilitymentioning
confidence: 99%